HOW TO IMPROVE STUDENTS’ ENGLISH COMMUNICATIVE SKILLS OF THE ELEVENTH GRADE OF MAN NGRAMBE NGAWI - Juaini, Juaini (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2016)
At present, speaking a foreign language represents one of the essential requirements of today´s society. Besides other skills and knowledge, it is considered as one of the most influencing factors while applying for a job or sustaining in a particular work position under the condition of advancing the language level. Based on my work experience, I can confirm that knowing a foreign language is a necessity for everyone in general, mainly for my students studentss. These people are required to reach a sufficient level in a foreign language in order to accomplish student assignments in missions abroad. Teaching foreign languages, mainly English, for these studentpurposes is provided by the Education Language Institute in MAN Ngrambe where I have been working as an English teacher for almost tenth years. My principal goal is to provide the students with as efficient English lessons as possible because it will be them who will have to deal with international relationships and take measures for solving various situations.The main reason for choosing this topic for my bachelor article was realizing how important speaking is in every day situations. No matter where we are, either in the Indonesia or in a foreign country, English conversation plays a crucial role in understanding each other and dealing with different kinds of uncovered problems. It means that not only students that I teach, need English for communication abroad but also Indonesia teachers need English to communicate with their colleagues native speakers. At my work I have an opportunity to encounter with people from various parts of the world and I am very interested in the way they use English as their mother tongue. These co-workers have a greater supporting role in our teaching process and it is always valuable to have a chat with them and ask questions to make sure our judgement was right. Even if they come from various areas in indonesia and their accents differ, it is just a question of time for teachers and also students to adjust to their speech and distinguish differences in pronunciation. Keywords: Speaking skill, Communicative Language Teaching (CLT), CAR